Postoperative venous thromboembolism and mortality in patients with pancreatic surgery. Issue 3 (20th June 2019) - Majmudar, Kaushal; Quintero, Luis D.; Fuentes, Harry E.; Stocker, Susan; Tafur, Alfonso J.; Lee, Cheong J.; Talamonti, Mark
Abstract: Background and Objectives: Pancreatic cancer is strongly associated with thrombosis. We investigated early postoperative venous thromboembolism (PVTE) mortality among patients with pancreatic surgery and compared outcomes in adenocarcinoma pancreatic cancer (ACPC) to non‐adenocarcinoma pancreatic neoplasm (NACPN). Methods: We analyzed a prospectively collected database of patients who underwent pancreatic cancer or neoplasm‐related surgery. As NACPN is underrepresented in other studies, we selected NACPN patients and a random sample of ACPC patients. PVTE was defined as VTE occurring within 3 months of surgical intervention. Statistical analysis was performed using Cox proportional hazards regression. Results: A total of 441 pancreatic surgery patients were included, with 331 ACPC and 110 NACPN. Median follow‐up was 449 days during which 90 (20.4%) patients developed VTE. PVTE occurred in 53 (12.0%) patients, including 41 (12.4%) ACPC patients and 12 (10.9%) NACPN patients. Those with PVTE had 60% higher mortality rate. A multivariable analysis found that PVTE is an independent predictor of increased mortality (HR Adj, 1.6; 95% CI, 1.1‐2.2; P < .01). The mortality impact was not consistent between ACPC (HR, 3.2; 95% CI, 1.3‐7.9) and NACPN groups (HR, 1.3; 95% CI, 0.9‐1.8). Conclusions: Postoperative venous thromboembolism is an independent predictor of increased mortality in pancreatic surgery, specifically in adenocarcinoma pancreatic cancer surgery.